An Archaeology of Semiotic Perspectives on Tourism - Bassano, Giuditta (E|C, 2022)
The contribution aims to offer a panorama of semiotic problems concerning tourism phenomena. At the same time it seeks to identify different approaches in the semiotic study of tourism. From a fìrst moment in which semiotics dealt with tourism through the lens of a criticai discourse, the panorama evolved towards a broader perspective, which considers nowadays tourism as a field of analysis. Far this latter conception, certain aspects of the tourism phenomena in its most generai sense and their specific inherence to semiotic theory are highlighted: 1. oxymoronicity; 2. the relationship between phenomenology and narrative structures; 3. the relationship between tourism experience and memory; 4. the role of new technologies within the tourism experience. Furthermore, an aspect linking memory studies and tourism studies is brought into focus. A final session concerns a brief presentation of the volume's essays.